Gut Microbiome and Its Influence On Ocular Surface and Ocular Surface Diseases. Issue 7 (17th July 2022) - Thakur, Shambhawi; Sheppard, John D.
Abstract: The gut microbiome plays a substantial immunologic and pathophysiologic role in maintaining the health of the host, and dysregulation of this dynamic ecosystem has been associated with several inflammatory conditions. Many studies have explored the influence of gut microbiota on the ocular surface and whether gut microbiota impact the pathophysiology of ophthalmic conditions. These findings have highlighted the advantages of enhancing gut microbes through probiotics, prebiotics, diet, vitamin supplementations, and fecal microbial transplant in clinical practice. The purpose of this review article was to provide an up-to-date overview of the knowledge on this topic. Further exploration of this area of research is important to help guide new therapeutic targets to develop treatment and prevention of certain ocular surface diseases.